The Prevalence of Pulmonary Hypertension in Destroyed Lung Due to Post Pulmonary Tuberculosis and Its Relation to Exercise Capacity - Diana Septiyanti; Astari Pranindya Sari; Wahju Aniwidyaningsih; Budhi Antariksa; Bambang Budi Siswanto (Jurnal Respirologi Indonesia, 2018)
Background: To improve patient’s quality of life, understanding destroyed lung (DL) is very important, however, it is very limited in information related to it as well as to the existency of pulmonary hypertension (PH) in destroyed lung. In this study, we investigated relationship between DL with PH status and the exercise capacity through 6 minutes walking test (6MWT). Method: Cross-sectional analytic study involving 54 DL subjects. Subjects performed echocardiography to exclude cardiac abnormality and to determine whether they had PH. Subjects were then divided into two groups based on their PH status. They underwent 6MWT and their walking distance and peripheral oxygen saturation were measured. Student t-test was used for analyzing data. Furthermore, we determined correlation between walking distance and mean Pulmonary Artery Pressure (mPAP) value also peripheral oxygen saturation and mPAP. Result: We calculated the mean of walking distance between the two groups. The mean from subjects with PH and without PH were 329.18 and 388.77 meter respectively (p=0.035). We found negative correlation between the mean of walking distance and subject’s mPAP using statistical analysis Pearson correlation test (r= -0,457, p = 0,001) while percentage of 6MWT by its prediction also had a negative correlation (r= -0,468, p=